Dido and Aeneas: An Archetypical Myth at the Roots of the Cultural Dialogue between the Two Shores of the Mediterranean - Iulietto, Maria Nicole (European Journal of Multidisciplinary Studies, 2018)
The aim of this paper is to examine the famous Virgilian myth of Dido, queen of Carthage, and Aeneas, the legendary ancestor of Rome, as an archetype of the cultural dialogue between different Mediterranean cultures. Not only will this allow us to underline the preeminent role of the classical heritage in the construction of the European identity, but also to demonstrate how this ancient legend, dealing with very current topic such as interculturality, immigration and hospitality – which appear, on a lexical level, in the insistence on such terms as sociare, miscere, iungere in the first (as well as in the fourth) book of the Aeneid – should be still deserving attention by scholars and European citizens in general.